A view on possible regime shifts in the North Atlantic subpolar gyre in the mid 1920s and 1990s - Lotsberg, Emilie Otilde (The University of Bergen, 2014)
There is strong observational support for two significant warming episodes of the North Atlantic Subpolar Gyre (SPG), one starting in the mid 1920s the other in the mid 1990s. Possible mechanisms responsible for the two warming events are investigated and compared using hind cast simulations with a state-of-the-art global Ocean General Circulation Model (OGCM). The OGCM was forced by an adjusted variant of the Twentieth Century Reanalysis version 2 (20CRv2) for the period 1871--2009. It is found that the preconditioning of the ocean was an essential component for the observed warming and the decline in the SPG circulation in the mid 1920s and the mid 1990s. Both preconditioning phases are characterised by positive North Atlantic Oscillation (NAO) forcing and by that cooling of the surface waters, and subsequent enhanced production of intermediate to deep water masses in the SPG region. The latter causes a lagged intensification of the Atlantic Meridional Overturning Circulation (AMOC) and by that, increased poleward transport of warm, saline waters of subtropical origin. In addition, a reduction in the NAO forcing following the mid 1920s and mid 1990s contributed to the warming. The preconditioning of the 1990s warming was stronger than that for the 1920s warming. As a consequence, the shift in the marine climate in the 1990s was more abrupt and stronger than the 1920s counterpart. Sensitivity experiments have been run in order to examine the role of the atmospheric forcing for the two warming events. From and including 1920 and 1990, the ocean was in these cases forced by a constructed atmospheric field dominated by winters with negative NAO forcing. It is found that negative NAO forcing is important for the onset of the warming, but that the ocean preconditioning determines the magnitude of the shift in the ocean climate in the SPG region. The conducted sensitivity experiments suggest that the preconditioning of the ocean prior to 1990 could have been sufficient to initiate a comparable collapse of the gyre as ...